KNOWLEDGE AND PRACTISE REGARDING DOGS AND RABIES AMONG FULANI CATTLE HERDING COMMUNITIES IN ZARIA ENVIRONS, NIGERIA - Dzikwi; Umoh (International Journal of Research -GRANTHAALAYAH, 2017)
Rabies is a viral disease transmitted mainly following the bite of a rabid dog. Dogs are increasingly being kept for security of livestock among cattle herders. The study was conducted to assess the knowledge, attitude and practise regarding dogs and rabies among the cattle herding community to identify gaps regarding knowledge of rabies transmission and plan intervention. Questionnaires were prepared and administered by face to face interview among members of the communities. Responses were scored based on a marking scheme and observations documented. There was poor knowledge and bad practise regarding rabies and dog ownership. Most of the dogs were not vaccinated against rabies. Furthermore, there was a practice of swapping dogs for household items among members of the community and dog dealers. This has grave implication because it will drive reckless dog ownership for the sole purpose of obtaining desired household items. This coupled with poor vaccination of dogs will lead to increased chances of rabies transmission. There is a need for educating this group on the role of dogs in rabies and vaccination of the dogs in the community.